IMPACT OF E-FILING AND E-BILING ON TAX COMPLIANCE BEHAVIOR - Yanto, Thesya Ferdy; Girindratama, Muhammad Wisnu (Jurnal Riset Terapan Akuntansi, 2025)
This study aims to analyze the influence of digital tax administration, particularly the implementation of e-Filing and e-Billing, on taxpayer compliance at the Tax Office (KPP) in the Gubeng area of Surabaya. The implementation of electronic tax services is expected to enhance compliance through greater convenience, transparency, and administrative efficiency. This research employs a quantitative approach, utilizing primary data collected through structured questionnaires distributed to registered individual and corporate taxpayers. The data were analyzed using multiple linear regression to examine the impact of e-Filing and e-Billing on taxpayer compliance. The results indicate that neither e-Filing nor e-Billing has a statistically significant effect on taxpayer compliance. These findings suggest that other factors—such as tax knowledge, the effectiveness of law enforcement, or taxpayer attitudes—may play a more dominant role in shaping compliance behavior. Keywords:  E-Biling, E-Filing, Tax Administration System, Taxpayer Compliance